Non-Linear Time History Analysis of Moment Frame Structure with Performance-Based Approach on Different Concrete Compressive Strengths - ZAIDI, SYED HASSAAN AHMED (2023)
The non-linear time history analysis and Pushover analysis are performed on the two models of different compressive strengths but of the same element and component sizes by keeping the same reinforcement arrangement. The concrete strengths were 30Mpa and 40Mpa. The structure was first analysed based on the linear model approach with the two compressive strengths 30Mpa and 40Mpa in SAP2000 by following the code ACI318. The two nonlinear model were then analysed in the Perform3D. For the modelling of the beams, the plastic hinge modelling approach was used. The modelling of the column was done on the fibre hinge modeling approach. The structure is 7 stories high, and it has a footprint of 50 x 50 m. Each bay is 5 meters. The nonlinear concrete model was constructed based on the Razvi (1992) confined mode. All of the seven earthquakes were scaled for the design response spectrum. The results show a trend in the better performance of 40Mpa structure over 30Mpa. The 30Mpa structure reaches the Immediate Occupancy level earlier than the 40 Mpa structure. The energy consumption patterns do not show any trend or similarity. Usage ratios were found significantly lower in the 40Mpa structure, especially at the Immediate Occupancy level in all of the seven earthquakes. The 40Mpa structure has predominantly less drifts the 30Mpa structure. Keywords: Performance Based Design, PBD, Perform3D, time history analysis, pushover analysis, nonlinear concrete, concrete compressive strength